The Mechanical Properties and the Threshing Damage and Its Effects on Nutritional Quality of Buckwheat Grains - Yun Liu; Yang Zhang; Lufei Yang; Shuai Feng; Haoran Yan; Decong Zheng (Agronomy)
Buckwheat grains will suffer varying degrees of damage during the threshing process. Damaged grains are prone to changes in nutritional quality during storage. To explore the relationship between the threshing damage mechanism and nutritional quality, the mechanical properties of buckwheat with different moisture contents were determined through compression and friction tests, obtaining some conventional mechanical property indicators. On this basis, a 3D collision model of buckwheat–nail tooth was established, and the dynamic process of collision was simulated with LS-DYNA. During collision, the changes in energy, von Mises stress, and critical damage velocity of grains with different moisture contents were analyzed. After the threshing test, the grains were observed and classified according to the degree of damage. The differences in nutritional components of different types of grains were analyzed through physicochemical experiments. The experimental results showed that the failure force, elastic modulus, and ultimate strength of buckwheat grains were negatively correlated with moisture content, while the deformation and friction coefficient were positively correlated with moisture content. During collision, the von Mises stress of the grains showed a pattern of increase and then decrease. The maximum stress value occurred at the contact area center, spreading along the periphery and gradually decreasing. The maximum von Mises stress decreased with increasing moisture content and increased with increasing collision velocity. The critical damage velocities of grains at moisture contents of 11.98%, 15.77%, 18.04%, 20.82%, and 25.22% were 13.07, 11.72, 10.94, 10.55, and 10.15 m/s, respectively. After threshing, grains were divided into three types: undamaged, surface cracked, and shell damaged. The nutritional quality of the last two damaged grains decreased during the storage process. These results are of great significance for optimizing buckwheat threshing parameters, reducing buckwheat damage, and improving the economic performance of the buckwheat industry.